ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL STATISTIKA DI KELAS XII MIPA SMA N 1 KECAMATAN GUNUANG OMEH - Dety Ramadhani; Isnaniah Isnaniah; Sari Desiana Putri (KOLONI, 2022)
Mathematics is the queen or source of science from other educational sciences, with other purposes. Mathematics as an educational science stands up and develops for itself and can meet other science needs in the development of science. Statistics is one of the materials to be studied in mathematics because, statistics is an important subject to study, it is one of the core materials in the 2013 curriculum. Statistics is the study of a set of ways or rules relating to analysis, collection, inference of data consisting of numbers using a specific assumption. The purpose of this study was to analyze and identify the weaknesses of students or to determine the cause of students mistake in resolving statistical matters. This study used qualitative research methods with an exploratory descriptive approach. The subjects of this study were randomly selected students as many as six people from class XII MIPA . Data collection using documentation conduct diagnostic tests to students and interviews. The result of this study are the types of mistakes students make in solving statistic, namely: concept errors 36,36 %, error formula 18,18 %, error in calculation 18,18 %, error in completion process 27,27 % and subject in this study have not yet been widely understood statistical material in terms of maximum data layout size and data spread size. Because in solving the test problem the subject still makes many mistakes in solving the problem. Keywords: Mathematics, Errors, Statistics, Analysis, Students.